Activity of ï¡-terpineol as a potential anticancer candidate: cytotoxicity, proapoptotic and antiproliferative evaluation in TD47 cell lines - Mustofa, Puguh Indrasetiawan Indwiani Astuti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2012)
Previous study has shown that ï¡-terpineol has a cytotoxic effect on NCI-H69 cancer cell line.This study aimed to evaluate cytotoxicity, proapoptotic, and antiproliferative activities of ï¡-terpineol in T47D cell lines. The cytotoxic activity of ï¡-terpineol was determined using MTT cellviability assay, while apoptosis was tested by the acridine orange-ethidium bromide stainingmethod. The cell cycle was evaluated by flowcytometry method. The results showed that ï¡-terpineol had cytotoxic effect on the T47D cells with the IC50 value of 135.00 Â± 8.74 ïM.Furthermore, ï¡-terpineol induced the cells apoptosis in a dose-dependent manner. Flowcytometryanalysis showed that ï¡-terpineol induced the T47D cell distribution in Go/G1 phase, howeverinhibited cell distribution in S phase. This study suggests that ï¡-terpineol has a potential anticanceractivity.